Privacy protection legislative scenario in select countries - Bhasin, Madan Lal (Center for Academic Research, 2016)
The right of privacy is well established in international law.In fact, consumer privacy has attracted the widespread attention of regulators across the globe. Of course, privacy laws vary throughout the globe but, unfortunately, it has turned out to be the subject of legal contention between the European Union (EU) and the United States (US).Protection of personal data privacy under the law has been shaped by the interests of multiple constituencies: individuals, commercial organizations, government agencies, law enforcement, and national security services.For corporations that collect and use personal information, now ignoring privacy legislative and regulatory warning signs can prove to be a costly mistake. One of the greatest challenges faced by privacy and data protection professionals is demonstrating that their organizations have complied with the requirements of the various laws governing the handling of personal data. The freshly revised BS10012 can help organizations to meet their privacy management obligations. This is an exploratory, descriptive and qualitative study using secondary sources of data.Here, an attempt has been made to briefly acquaint the readers’ with the privacy laws prevalent in select countries.It is expected that a growing number of countries will adopt privacy laws to foster e-commerce.Undoubtedly, accountability for privacy and personal data protection needs to be a joint-effort among governments, privacy commissioners, organizations and individuals themselves. Legislators all over the world have taken notice and tried to minimize invasion of privacy but without much success.